Identifikasi Senyawa Aktif Ekstrak Daun Tembakau (Nicotiana tabacum L.) Sebagai Antibakteri Terhadap S. aureus (ATCC 25923) - Anis Uswatun Khasanah; Sri Juni Nastiti (Al-Hayat, 2021)
Tobacco leaf contains bioactive compounds as antibacterial. Staphylococcus aureus is a pathogenic bacteria causing several infection  diseases. The purpose of this study was to identify the active compounds group that have antibacterial against and determine the optimum  concentration which was able to inhibit S.aureus ATCC 25923 activity in tobacco leaf extract. The assay of inhibitory activity of tobacco leaf extract was carried out qualitatively using diffusion disc method at various concentration of tobacco leaf extract; 40, 50, 60, 70, 80, 90, and 100%. Gradual maceration (M2) and total maceration were used to perform the extraction process, using methanol 70% and etanol 96% as the solvent. Thin Layer Chromatografi (TLC) assay were carried out to identify the bioactive compounds. The results showed that the methanol (M2) and etanol (E) extract of tobacco leaf had antibacterial avtivity against S.aureus. Their bactericidal activity (inner diameter of inhibition) was 12,5 mm, and bacteriostatic (outer diameter inhibition) was 20 mm. The optimum concentration of antibacterial methanol extract was 50%, and the optimum concentration of antibacterial etanol extract was 60%. It was found that the antibacterial compound was detected as flavonoid and terpenoid.